Exploring the Mechanism of Sustainable Innovation in the Complex System: A Case Study - Yuanyuan Chu (Systems)
The construction of complex systems is of great significance in enhancing national competitiveness and promoting social development. However, the academic community currently lacks a systematic understanding of its sustainable innovation mechanism. This study selected the China Manned Space Engineering Application System (CMSEAS) as a representative case of a complex system. Research data were collected by a multi-method approach including document literature, internal data, field research, and interviews. Through the lens of grounded theory, the study delves into how the complex system achieves local innovation and how to maintain the sustainability of innovation. Findings indicate that, firstly, late-mover advantage and spiritual strength jointly contribute to the knowledge accumulation of national major task-oriented complex systems, and this knowledge accumulation significantly improves the innovation ability of complex systems. Secondly, while emphasizing the enhancement of innovation capabilities, it is imperative for complex systems to implement holistic risk management, which is an important guarantee for successfully achieving the goal. Thirdly, in the context of market failure, the whole nation system provides strong support for the national major task-oriented complex system. The overall institution and overall capacity constitute the backbone for ensuring sustainable innovation.